Schwannomas of the head and neck - Anastasios Kanatas; Thomas Mucke; David Houghton; David A. Mitchell (Frontiers Media S.A., 2011)
Schwannomas are benign encapsulated nerve sheath tumors composed of Schwann cells. Malignant change in head and neck schwannomas is rare, with the incidence varying between 8 and 13.9%. In this review, we discuss the presentation and the management of head and neck schwannomas. The issues and difficulties based on our own experience as well as the experience of published reports from the literature are presented.